2020
DOI: 10.1111/jocs.15240
|View full text |Cite
|
Sign up to set email alerts
|

Center‐level CABG and valve operative outcomes and volume–outcome relationships in New York State

Abstract: Background: We analyzed center-level outcome correlations between valve surgery and coronary artery bypass graft (CABG) in New York (NY) State and how volume-outcome effect differ between case types. Methods: We used the 2014-2016 NY cardiac surgery outcomes report. Centerlevel observed to-expected (observed-to-expected ratio [O/E]) ratio for operative mortality provided risk-adjusted operative outcomes for isolated CABG and valve operations. Correlation coefficient characterized the concordance in center-leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The association between procedure volume and outcomes has been established for other cardiovascular procedures including transcatheter aortic valve replacement 10 , implantable cardioverter defibrillator implantation 9 , percutaneous coronary intervention 8 , coronary artery bypass surgery 5 , and mitral valve surgery 6 . In this study, we observed a significant relationship between hospital and physician procedure volume and acute procedural success and safety.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The association between procedure volume and outcomes has been established for other cardiovascular procedures including transcatheter aortic valve replacement 10 , implantable cardioverter defibrillator implantation 9 , percutaneous coronary intervention 8 , coronary artery bypass surgery 5 , and mitral valve surgery 6 . In this study, we observed a significant relationship between hospital and physician procedure volume and acute procedural success and safety.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, underreporting is possible in this voluntary registry, although the NCDR used a rigorous data quality reporting process that includes audits of adverse events at 5% of sites annually using manual review of medical records and billing codes. The association between procedure volume and outcomes has been established for other cardiovascular procedures including transcatheter aortic valve replacement 10 , implantable cardioverter defibrillator implantation 9 , percutaneous coronary intervention 8 , coronary artery bypass surgery 5 , and mitral valve surgery 6 . In this study, we observed a significant relationship between hospital and physician procedure volume and acute procedural success and safety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation